Multiplicación de plantas nativas de la costa del Río de la Plata - Miranda, Marcelo Ademar; Zúcaro, Matilde (Estación Experimental Agropecuaria Área Metropolitana de Buenos Aires, INTA, 2024)
Native Plants grow forming more or less homogeneous plant communities and constitute – as primary Producers – a fundamental part of the ecosystems originating from a certain place. We find these communities in those environments with little or no human intervention, protected areas and where the characteristics of the natural environment (soils and ecosystem pulses) are conserved. They are recognized by their general appearance or physiognomy and by their species composition; They are popularly identified as: Pajonales, Matorrales, Talales, Montes, etc. Not all plants that grow spontaneously or wild are native to that place, some have arrived from other regions of the planet, which are “wild” and can even displace the site's own or original vegetation. The interest in its cultivation is largely due to the active process of biodiversity loss that exists in most of the environments of the Buenos Aires Metropolitan Area (AMBA). The “native” ones are part of the natural heritage that we must preserve and share with future generations. With their cultivation, the link between the population and the environment is strengthened, and the ancestral knowledge of the native peoples is revalued, who named them and used them for different uses: food, medicine, architecture, clothing, etc., and preserved them to this day. days. They fulfill relevant functions in the control of environmental pulses, providing populations with important ecosystem services, such as the control of excess water or the recharge of aquifers. They currently represent a gardening and landscaping sector with growing demand. They contribute to the agro-biodiversity of productive plots and form bio-corridors that counteract the excessive fragmentation of “natural” environments. This guide attempts to guide those growers who are starting out and are interested in forming a native plant nursery on a family scale, a productive enterprise or for environmental training1. It is largely nourished by the knowledge shared by many growers.